METODE ANALISIS BOWTIE UNTUK RISIKO KECELAKAAN KERJA PADA PROYEK BEPI OFFICE - Della Widyanti (Jurnal Vokasi Teknik Sipil, 2024)
The construction of high-rise buildings is one of the developments that have the highest risk of work accidents. If the methods used are inappropriate or inaccurate, it can lead to work accidents, which are unexpected events. To avoid the risk of work accidents, project managers must be able to manage risks so that they do not have a fatal impact on achieving project goals. Effective risk management is essential to identify, evaluate, and manage the risk of work accidents at the project site. Based on the background explanation that has been given, the purpose of the research is to identify the main risk factors, causes, and risk mitigation measures in the construction of the Bepi Office building using the Importance Index (IMPI) and Bowtie Analysis methods. There are two main risks that fall into the high-risk category, namely workers being hit by land clearing materials and workers being exposed to reinforcing wires.